Notes from the underground: interpretative problems - Villaça, Davi Lopes (RUS (Sao Paulo), 2021)
Beginning with a discussion of the difficulties involved in the analysis of Dostoevsky's Notes from Underground (1864) as manifested at times in the history of the novel's interpretation, this article develops a series of reflections about the complex relationship between the author and his narrator, analyzing their points of identification and opposition and entering into dialogue with various critical approaches to this subject.